Phraseologization of Internet memes - Syzonov , Dmytro (Current issues of Ukrainian linguistics: theory and practice, 2023)
The article analyzes modern Internet memes, which, due to their precedent, are able to be phraseologized in mass communication. Memes are considered intertextual polycode units that arise as a verbalized reflection on the dynamic development of events and actively function in the virtual media space. It has been proven that the language of Internet memes is built on irony and sarcasm using stylistic puns and "word games", oxymorons and gradation techniques, as well as aphorisms, precedent quotes, established constructions. A special emphasis is placed on war memes, which are characterized, in our opinion, by a set of primary features: (a) a catchy word, expression, verbal / non-verbal sign must be precedents; (b) spontaneity in appearance; (c) flexibility to modifications in order to interpret different events and phenomena; (d) appeal to the background knowledge of recipients; (e) semantic unity in form and content; (e) reproduction of cultural memory and response to the digital challenges of modernity. All this enables Internet memes in language communication to phraseologize and be able to be widely replicated in the information space. It is emphasized that communicators can independently create Internet memes and distribute them on their own media resources, which emphasizes the ability of memes to be constantly modified. For illustrative material, we turned to the information of the "Ukrainian Cultural Heritage Online" (SUCHO) portal, which has more than 10,000 memes as cultural markers of Ukraine. Having analyzed the memes of 2023, we can state that most Internet memes are precedent phenomena of the modern media space, and therefore have the ability to phraseologize. Therefore, Internet memes are a powerful source of new phraseology, have the ability to stylistically transform and help to strengthen the impression of a relevant informational message.
Keywords: internet meme; media phraseology; electronic communication; media linguistics; innovative linguistics.